Scientific approach to the development filled elastomeric materials applied in aviation - Масленнікова, Л.Д.; Іванов, С.В.; Столярова, Н.В. (Proceedings of National Aviation University (archive), 2005)
The results of latex structure investigation by means of optical microscopy had been presented of low dilution by water. The micelles obtained have not close packed structure. Statistical polyisopren macromolecules balls of natural latex had been studied by UF-spectroscopy of high dilution.